2020
DOI: 10.1002/jhbp.750
|View full text |Cite
|
Sign up to set email alerts
|

Impact of postoperative bile leakage on long‐term outcome in patients following liver resection for hepatocellular carcinoma

Abstract: Liver resection in patients with hepatocellular carcinoma (HCC) has traditionally been associated with high morbidity and mortality. 1 With recent improvements in surgical techniques and perioperative management, there has been a marked reduction in morbidity and mortality during liver resection. 2 However, bile leakage following liver resection is a common and disturbing complication that occurs in a significant number of patients, resulting in a prolonged intensive care and hospital stay. The prevalence of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
1
13
2
Order By: Relevance
“…In order to evaluate the effect of postoperative BT more equitably, analysis by prospective study is desired. Third, bile leakage has been reported to have an adverse effect on overall survival [15], however, present study showed no worse relationship between bile leakage and long-term survival. In our hospital, if the bilirubin level in drainage fluid is at least five times that of serum bilirubin, we perform a repeat laparotomy as early as possible to repair the bile leakage.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…In order to evaluate the effect of postoperative BT more equitably, analysis by prospective study is desired. Third, bile leakage has been reported to have an adverse effect on overall survival [15], however, present study showed no worse relationship between bile leakage and long-term survival. In our hospital, if the bilirubin level in drainage fluid is at least five times that of serum bilirubin, we perform a repeat laparotomy as early as possible to repair the bile leakage.…”
Section: Discussioncontrasting
confidence: 71%
“…There have been only limited studies of the association between short-term and long-term outcomes after LR [14][15][16][17][18][19][20][21], although bile leakage [15,16], red blood cell transfusion (BT) [17][18][19][20], and intraperitoneal hemorrhage [21] have been shown to be complications that adversely affect long-term survival. However, which postoperative complications are long-term prognostic factors is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…24 Yamamoto et al in a study evaluating the long-term impact of BL after liver resection for HCC found that post-operative BL was strongly associated with poorer OS and DFS following liver resection and may contribute to our understanding of the requirements for preventing BL and developing strategies towards achieving improved treatment outcomes of postoperative BL. 25 The current study has several limitations including its retrospective nature; it included data from a single center, and it included limited number of patients. Also, the number of bile leakage events was relatively small.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal infection due to bile leakage after surgery occurred in 10 patients. The influence of bile leakage ranges from a ripple to a shock, which should not be neglected 26 . Careful evaluation during operation is necessary to prevent the occurrence of bile leakage 27 .…”
Section: Discussionmentioning
confidence: 99%